2013
DOI: 10.1007/s13280-013-0470-y
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Land-Sharing and Land-Sparing Conservation Strategies Through Regional Networking: The Mesoamerican Biological Corridor as a Lifeline for Carnivores in El Salvador

Abstract: Nations with little remaining natural habitat and small extent are challenged when trying to achieve biodiversity targets. We show that the Central American nation of El Salvador cannot viably sustain populations of 87 % of its extant carnivores, especially in the case of large-bodied species with low population densities. Current land-sparing strategies will not suffice; therefore we propose that land-sharing strategies be implemented in tandem with protected areas to expand current conservation efforts via n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…It would be useful to understand when such studies inform conservation planning and land‐use decision making on the ground. In some countries, such as El Salvador, it is clear that this debate is not useful because there is so little forest left that El Salvador would have to both protect all of its existing forests and improve the landscape matrix through wildlife‐friendly agriculture to promote connectivity, in order to contribute to a regional network for carnivore conservation . Thus, in El Salvador, a “both‐and” framing is more useful than an either‐or framing for policy development.…”
Section: Do Ecological Field Studies Resolve the Sparing–sharing Debate?mentioning
confidence: 99%
See 1 more Smart Citation
“…It would be useful to understand when such studies inform conservation planning and land‐use decision making on the ground. In some countries, such as El Salvador, it is clear that this debate is not useful because there is so little forest left that El Salvador would have to both protect all of its existing forests and improve the landscape matrix through wildlife‐friendly agriculture to promote connectivity, in order to contribute to a regional network for carnivore conservation . Thus, in El Salvador, a “both‐and” framing is more useful than an either‐or framing for policy development.…”
Section: Do Ecological Field Studies Resolve the Sparing–sharing Debate?mentioning
confidence: 99%
“…Thus, the sharing–sparing dichotomy may force conservation biologists into a choice between two undesirable alternatives. Instead of an either‐or framework, a “both‐and” framework could lead toward a scenario that most if not all conservationists could get behind—large protected areas surrounded by a relatively wildlife‐friendly matrix promoting connectivity through a combination of favorable land uses and corridors . How to get there is a question worth asking, and getting there is a goal worth striving for.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that the sparing-sharing model is irrelevant in regions where little intact native vegetation remains, including temperate regions [13], the Brazilian Atlantic Forest [139], or El Salvador [20,140], and that actions in such regions should focus on land sharing. I disagree that this is a foregone conclusion.…”
Section: Land Sparing In Heavily-modified Landscapesmentioning
confidence: 99%
“…It builds on previous reviews and classifications such as that of Kamal et al (2015a) by separating the components of successful private conservation into a series of successive stages, seen here as hurdles, which must be surmounted in sequence. As outlined in the Introduction, previous studies have considered ecological (Crespin and García-Villalta, 2014), legal (Rissman, 2013), social (Knight et al, 2010;Raymond and Brown, 2011), and economic (Phalan et al, 2011) aspects, but none has previously assembled these into a combined model which shows how an NGO (Pasquini et al, 2011;Stroman and Kreuter, 2014) can most effectively leverage its limited financial and political resources. We propose that this model is sufficiently general to be applicable across a wide range of biomes and ecosystems, jurisdictions and legal systems, countries and cultures, and socioeconomic situations.…”
Section: Discussionmentioning
confidence: 99%
“…One of the principal ecological objectives is the establishment of corridors and connections between existing reserves (Crespin and García-Villalta, 2014), and one of the key economic issues is the opportunity cost of forgoing agricultural development (Phalan et al, 2011). One of the key social mechanisms is through peer exchange and outreach (Kueper et al, 2013), and NGO's may play a critical role in these processes (Pasquini et al, 2011;Stroman and Kreuter, 2014).…”
Section: Introductionmentioning
confidence: 99%